Agricultural Commodity Exchanges in Latin America and the Caribbean - Arias, Diego; Ferreira Lamas, Alfredo; Kpaka, Musa (World Bank, Washington, DC, 2014)
A commodity exchange is a goods and financial market where different groups of participants trade commodities and commodity-linked contracts, with the underlying objective of transferring exposure to commodity price risks (UNCTAD). A commodity exchange that only trades goods is known as a physical or 'cash or forward' market, while the exchange that trades price derivatives is known as financial or 'futures and options' market (see Glossary for detailed definitions). Some agriculture commodity exchanges have both. Agricultural commodity exchanges date as far back as the early 18th century. Modern exchanges, notably the Chicago Board of Trade (CBOT) was created in 1848, recently merged with the Chicago Mercantile Exchange (CME), is one the oldest and most successful futures exchanges worldwide. Today several agricultural commodity exchanges exist throughout the Latin America and Caribbean (LAC) region. They facilitate trade and financial products in countries whose economies have a relatively large share of primary and secondary agricultural activities or either account for auctions on substantial food imports. This report looks at the current development of agricultural commodity exchanges in the LAC region and offers public policy recommendations that can foster the development of such exchange markets.